Development of encapsulated air microparticles using spray drying and sessile single droplet drying - Che Ku Jusoh, Tengku Farizan Izzi (2021)
The aim of this research was to produce spray dried particles with one large vacuole and controlled surface wettability, also known as encapsulated air microparticles, to be potentially applied as the dispersed gas phase in foam-based processed foods. Droplets containing a mixture of the slightly hydrophobic and thus surface active gum Arabic (GA) and the hydrophilic maltodextrin (MD) was selected for the development of encapsulated air microparticles based on literature reports of hollow spray dried particles. A sessile single droplet drying (SDD) on a hydrophobic surface and spray drying with a two-fluid atomiser were employed to evaluate the impact of droplet compositions (ratio of GA:MD, solids concentration and DE-value of MD) and processing conditions (drying temperature and droplet size) on the particle formation and the wetting properties of the particles.